2009
DOI: 10.1002/rcm.4215
|View full text |Cite
|
Sign up to set email alerts
|

A rapid screening method for prenylated flavonoids with ultra‐high‐performance liquid chromatography/electrospray ionisation mass spectrometry in licorice root extracts

Abstract: Due to their substitution with an isoprenoid group, prenylated flavonoids have an increased affinity for biological membranes and target proteins, enhancing their potential bioactivity. Although many prenylated flavonoids have been described, there are no methods that specifically screen for their presence in complex mixtures, prior to purification. We describe a method based on ultra-high-performance liquid chromatography (UHPLC) with electrospray ionisation mass spectrometry (ESI-MS) that allows rapid screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 27 publications
(16 reference statements)
3
71
1
Order By: Relevance
“…The RSA obtained for the studied methanol/water extract (EC 50 The resultant blue colour is linearly correlated with the total reducing potential of electron-donating antioxidants, being measured spectrophotometrically at 700 nm. 55 The RP value obtained in the present study (EC 50 ¼ 129 mg mL À1 ) was similar to the one described by Tohma & Gulçin (2010) for aqueous (EC 45 ¼ 62 mg mL À1 ) and ethanolic (EC 76 ¼ 50 mg mL À1 )…”
Section: Evaluation Of Antioxidant Activitysupporting
confidence: 90%
See 1 more Smart Citation
“…The RSA obtained for the studied methanol/water extract (EC 50 The resultant blue colour is linearly correlated with the total reducing potential of electron-donating antioxidants, being measured spectrophotometrically at 700 nm. 55 The RP value obtained in the present study (EC 50 ¼ 129 mg mL À1 ) was similar to the one described by Tohma & Gulçin (2010) for aqueous (EC 45 ¼ 62 mg mL À1 ) and ethanolic (EC 76 ¼ 50 mg mL À1 )…”
Section: Evaluation Of Antioxidant Activitysupporting
confidence: 90%
“…Many papers have been published proling phenolic compounds in G. glabra samples from different origins and using different extraction methodologies, some of them cited in the previous discussion. 34,35,[37][38][39][40][41][42][43][44][45][46] However, from all of them, only Montoro et al (2011) presented quantitative results, although they cannot be compared with ours results since they are expressed differently (mg g À1 of dry plant), thus these authors revealed liquiritin apioside as the main avonoid present in their sample, which is in agreement with the sample studied herein. In our case, the results were expressed in mg g À1 of extract in order to relate the amounts of phenolic compounds found in the extract to the antioxidant activity.…”
Section: Finally It Was Not Possible To Identify Compound 11 With a supporting
confidence: 83%
“…Figure S1 As hows the chromatogram of the licorice root extract. As an example, the two-step purification of peak number 1, eluting at 13.7 min and identifieda s glabrene [18] (Table 1), is shown in Figure S1 Ba nd C. After purification by flash chromatography (Figure S1 Table 1). In addition, six compounds were purchased.B oth purifieda nd purchased compounds were analyzed by UHPLC-MS to verify their purities and to obtain their fragmentationp atternsi nM S 2 .U HPLC-MS analysiso fc ompound 5 (4'-O-methylglabridin) showed ap urity at 280 nm of 98 %; however,s ome impurities were visible in the NI and PI mode MS spectra.…”
Section: Resultsmentioning
confidence: 99%
“…[18] Five prenylated isoflavonoids ando ne prenylated flavonoid were purifiedf rom the licorice root extract in at wo-step purification procedure. Glabrone, the peak indicated with a star (Figure S1 A), could not be purified, and peak number 2, identified as glabridin, was not purified, because glabridin was commercially available.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation